Pemberian Bantuan Hukum Terhadap Tersangka Tindak Pidana Pelecehan Seksual Di Polsek Aru Tengah - Leinussa, Joses Sandhy; Toule, Elsa Rina Maya; Patty, Jetty Martje (SANISA: Jurnal Kreativitas Mahasiswa Hukum, 2023)
Introduction: Legal Aid in the criminal justice system plays a very important role in ensuring a fair and humane judicial process. Providing legal assistance in the form of legal advisory assistance for suspects in the investigation process is a means of supporting law enforcement in general.Purposes of the Research: The research used is a type of empirical juridical research, or what is called field research, namely studying the applicable legal provisions and what is happening in reality in society.Methods of the Research: The research method in this paper uses a normative juridical research type. The research approach used is a statutory approach, a conceptual approach and a case approach. The procedure for collecting legal materials uses primary legal materials and secondary legal materials through books, articles, journals and the writings of legal experts, as well as legal materials analysis techniques in this study using qualitative analysis techniques.Resulth/Findings/ Novelthy of the research: The results of the study show that what the author can take from the suspect to obtain legal assistance at the investigation level as regulated in Article 56 paragraph (1) of the Criminal Procedure Code as a legal obligation has not been optimally realized by the Central Aru Police investigators, this can be seen in the examination process at the investigation level. , and obstacles in providing legal assistance to suspects in cases of criminal acts of sexual harassment at the Central Aru Police Sector, namely the absence of clear implementation mechanisms and rules governing the willingness of legal advisors to be appointed as legal counsel for suspects or defendants as regulated in Article 56 paragraph (1) KUHAP.